ANALISIS MAJAS PADA CERITA PENDEK â€œMATAHARI PUN TAK BOSANâ€ KARYA DANIL GUSRIANTO - Mega Asih; Indra Permana; Yeni Rostikawati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
A short story or short story is a literary work that is dialectically related between reality and short stories, proving that from various angles short stories can be analyzed. This research was carried out because in the short story "Matahari pun Tak Bosan" by Danil Gusrianto which has several figures written from each series of stories in it. The problems discussed in this study are so that readers can receive knowledge about the elements of figure of speech that can be used as experiences and lessons in everyday life. Speech serves to generate term art, language art in a word or in written form and to make words and language more interesting. Speech serves to generate term art, language art in a word or in written form and to make words and language more interesting. This research is to analyze the figure of speech contained in the short story by reading and observing studying the short story content first, then marking and analyzing the text which is included in diction and figure of speech, with the terms that have been analyzed, various kinds of figure of speech are found in the contents of the story. Not Bored "Danil Gusrianto's work, namely personification, pleonasm, hyperbole, rhetoric, alliteration and climax. The stylistic approach contributes to research on diction and figure of speech is one of the main elements to achieve various forms of meaning of literary works, because literary works cannot be separated from the use of figure of speech to make it seem aesthetically pleasing. The writer concludes that the short story "Matahari pun Tak Bosan" by Danil Gusrianto is a short story that motivates and inspires its readers. This short story can be used as learning material, and is suitable for reading by all groups.